2007
DOI: 10.1016/j.biopsych.2006.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Children and Adolescents with Autism Exhibit Reduced MEG Steady-State Gamma Responses

Abstract: The production and/or maintenance of left hemispheric gamma oscillations appeared abnormal in participants with autism. We interpret these data as indicating that in autism, particular brain regions may be unable to generate the high-frequency activity likely necessary for binding and other forms of inter-regional interactions. These findings augment connectivity theories of autism with novel evidence that aberrations in local circuitry could underlie putative deficiencies in long-range neural communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
270
8
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 300 publications
(318 citation statements)
references
References 55 publications
30
270
8
2
Order By: Relevance
“…Our finding that the subjects with autism are less able to detect speech features when the task is manipulated in the temporal domain points to deficient left-hemisphere processing. This is in line with converging evidence from structural, ERP and MEG studies that point to other left hemisphere deficits in autism as well (Bruneau et al 2003;Lepisto et al 2006;Flagg et al 2005;Wilson et al 2006;Murias et al 2007) Compared with the pink noise condition, the ripple signal separation task was extended significantly in the spectral domain (see Methods section), which required additional right hemisphere involvement. The higher detection thresholds in this condition suggest that resolving the spectral components was the main bottleneck to perform the task, and equally so in both subject groups.…”
Section: Discussionsupporting
confidence: 84%
“…Our finding that the subjects with autism are less able to detect speech features when the task is manipulated in the temporal domain points to deficient left-hemisphere processing. This is in line with converging evidence from structural, ERP and MEG studies that point to other left hemisphere deficits in autism as well (Bruneau et al 2003;Lepisto et al 2006;Flagg et al 2005;Wilson et al 2006;Murias et al 2007) Compared with the pink noise condition, the ripple signal separation task was extended significantly in the spectral domain (see Methods section), which required additional right hemisphere involvement. The higher detection thresholds in this condition suggest that resolving the spectral components was the main bottleneck to perform the task, and equally so in both subject groups.…”
Section: Discussionsupporting
confidence: 84%
“…14,15 Widespread abnormalities in GABA A receptor activity was recently demonstrated in postmortem brain tissue samples from individuals with autism, with affected regions including parietal and frontal cortices and the cerebellum. 22 These findings are also consistent with neural connectivity studies suggesting a reduction of inhibitory cells in autism, 23,24 which operate as 'GABA-gated pacemakers for neocortical oscillatory activity' (Wilson et al 24 …”
Section: Discussionsupporting
confidence: 77%
“…Whitham and colleagues have suggested that frequency oscillations[20 Hz reflect myogenic artifacts [11]. Considering that our EEG epochs were carefully selected (i.e., free of myogenic artifacts), we believe that our results reflect an actual difference in gamma power between ASD and healthy controls, as was the case of several other studies investigating gamma activity in ASD [5,12,13]. Furthermore, when performing the analysis on the parietal and central electrodes only, electrodes less associated with myogenic artifacts, similar results were obtained.…”
Section: Discussionmentioning
confidence: 75%